Establishing the practice of birth companion in labour ward of a tertiary care centre in India—a quality improvement initiative. (3rd August 2021) - Bharti, Juhi; Kumari, Aprajita; Zangmo, Rinchen; Mathew, Sonia; Kumar, Sunesh; Sharma, Aparna K
Abstract : Background: Birth companion is a key component for providing respectful maternity care and has been recommended by WHO and Government of India. It is a low-cost beneficial intervention that is vital in improving quality of care during labour and delivery. Local problem: Despite the available evidence on benefits of birth companion, there was no policy on allowing birth companion at our hospital in the past. Methods and interventions: We aimed to establish the practice of allowing birth companions in all eligible women in labour ward from existing 0% to 50% in 6 weeks' duration. This study was conducted in the Department of Obstetrics and Gynaecology, All India Institute of Medical Sciences, New Delhi. A quality improvement (QI) team was formed, and after obtaining the baseline data, problems were analysed using fish bone chart. A new policy of allowing birth companion was made and efforts made to sensitise and train the doctors and nurses posted in labour ward. Changed ideas were executed in multiple plan-do-study-act (PDSA) cycles. Simple interventions such as dress code for birth companions, curtains for ensuring privacy, display of posters and frequent reminders on WhatsApp groups were planned . Results: The median value of women accompanied by birth companion marginally increased to 25% after the first PDSA cycle. Implementation of further changed ideas led to increase in median, which reached 66.6%. Thereafter, there was a decline, but by the end of 6 months, it was possible to attain the goal and sustain it. Conclusions: Simple steps of QI methodology can be used to address the prevalent problems in our healthcare. Implementation of any new practice comes with major challenges, but we could achieve our goal because of a motivated team working together on multiple changed ideas applied sequentially in PDSA cycles.